A systematic review of intracavernosal injection of mesenchymal stem cells for diabetic erectile dysfunction (Medical Journal of Indonesia, 2021)
BACKGROUND As current erectile dysfunction (ED) treatments are limited, other treatment such as stem cells should be explored. Hence, this study aimed to review the sources, method of administration, and therapeutic effect of mesenchymal stem cells (MSCs) for diabetic ED treatment. METHODS All relevant articles regarding the use of MSCs for diabetic ED were searched in PubMed and Google Scholar databases from December 15, 2019 to January 1, 2020 published in the past 10 years. The keywords were “mesenchymal stem cells” and “diabetic ED”. The selection and critical appraisal of the studies were discussed. Diabetic ED was evaluated for functional and structural outcome. Functional outcome in animal studies was assessed by intracavernosal pressure/mean arterial pressure (ICP/MAP) ratio, meanwhile the structural outcome was done microscopically. In human study, the assessments were done using international index of erectile function score (IIEF-5) to erection hardness score and penile Doppler ultrasonography. RESULTS There were 10 animal studies and 3 human studies. The studies used MSCs from adipose (n = 6), bone marrow (n = 4), placenta (n = 1), umbilical cord (n = 1), and muscle tissue (n = 1). The MSCs were administrated through intracavernosal injection in all studies. In all animal studies, functional outcome was improved, shown in higher ICP/MAP ratio. Microscopically, there were an increase of cavernosal endothelial cells, vascular endothelial growth factor, nitric oxide synthase, and smooth muscle cells. In human studies, IIEF-5 and erection hardness score were improved. Peak systolic velocity was also higher. CONCLUSIONS MSCs may be a promising therapy for diabetic ED; however, long-term safety concerns still need further investigations.